2023
DOI: 10.1007/s10453-022-09778-z
|View full text |Cite|
|
Sign up to set email alerts
|

Spore dispersal patterns of the ascomycete fungus Ramularia collo-cygni and their influence on disease epidemics

Abstract: Ramularia leaf spot is a major economic disease of barley caused by the dothidiomycete fungus Ramulariacollo-cygni. The fungus has a complex life cycle which includes extensive late season spore release events and a seed-borne phase. Predicting disease epidemics during the growing season remains a difficult challenge. To better understand the interaction between spore movement and disease epidemics, spore samplers were set up in Germany (two sites over 4 years), Poland (seven sites over 2 years) and the UK (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The moderate level of differentiation found between European populations supports the results of Stam et al. (2018) who suggested that European Rcc populations form one genetic cluster driven mainly by long‐distance spore dispersal (several kilometres; Brown & Hovmøller, 2002; Havis et al., 2023) and seed exchange between countries.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The moderate level of differentiation found between European populations supports the results of Stam et al. (2018) who suggested that European Rcc populations form one genetic cluster driven mainly by long‐distance spore dispersal (several kilometres; Brown & Hovmøller, 2002; Havis et al., 2023) and seed exchange between countries.…”
Section: Discussionsupporting
confidence: 76%
“…Significant differentiation (high to moderate) between all populations included in our study was observed, where the Argentinian population was highly and significantly differentiated from the others. The moderate level of differentiation found between European populations supports the results of Stam et al (2018) who suggested that European Rcc populations form one genetic cluster driven mainly by long-distance spore dispersal (several kilometres; Brown & Hovmøller, 2002;Havis et al, 2023) and seed exchange between countries.…”
Section: Groupsupporting
confidence: 76%
See 2 more Smart Citations
“…Collection and quantification of airborne fungal propagules are now routine and feature prominently in arriving at both prophylactic and therapeutic decisions for the management and control of plant diseases caused by aerially dispersed fungal inoculum 13,37,38 . Since the initial conception of Hirst‐type air samplers by Gregory 39 and Hirst 40 (reviewed by West and Kimber 41 ), advances in the coupling of the methods of aerobiology and techniques of wind‐dispersed fungal propagule collection, detection and quantification have enabled earlier, easier and more effective decisions in disease management 42–45 . Taken together, the integration of spore trapping with quantitative diagnostic assays such as qPCR can facilitate and enhance a faster and more accurate assessment than by abundance estimation made by spore counting on light microscope slides, particularly if these spores are difficult to identify visually at the species and infra‐species levels, which is very often the case with phytopathogens of important crop plants.…”
Section: Discussionmentioning
confidence: 99%